Jetted Seyfert Galaxies at z = 0: Simulating Feedback Effects on Galactic Morphology and Beyond - Julianne Goddard; Isaac Shlosman; Emilio Romano-Diaz (The Astrophysical Journal)
We use high-resolution cosmological zoom-in simulations to model feedback from Seyfert-type supermassive black hole (SMBH) jets onto galaxies with identical dark matter (DM) halos of log M / M _⊙  ∼ 11.8. The low-mass,  ∼10 ^6 M _⊙ , seed SMBHs have been introduced when the parent DM halos have reached log M / M _⊙  ∼ 11. In a controlled experiment, we vary only the efficiency of the SMBH accretion and focus on galaxies and their immediate environment properties. Our results show that the active galactic nucleus jet feedback has a substantial effect on the basic properties of Seyfert-type galaxies, such as morphology, gas fraction and distribution, star formation rate and distribution, B/D ratio, DM halo baryon fraction, and properties of the circumgalactic medium and beyond. These have been compared to a galaxy with supernovae only feedback. We focus on the energy deposition by the jet in the interstellar medium (ISM) and intergalactic gas medium, and follow the expansion of the multiple jet cocoons to ∼2 Mpc. We find that the jet–ISM interaction gradually pushes the star formation to larger radii with increasing accretion efficiency, which results in increased mass of the outer stellar disk, which is best fit as a double-exponential disk. Furthermore, we compare our galaxies and their properties with the observed nearby Seyfert galaxies, including the scaling relations, and find a close agreement, although statistical analysis of observed Seyferts is currently missing. In a forthcoming paper, we focus on the evolution of these objects at z ≲ 10 and study the effect of the SMBH seeding redshift.